Manufacturing method of high-air-tightness sealing laminated ring and sealing laminated ring
Through Si element microalloyation and low oxygen annealing, the problems of bending process defects, processing cracking risks and insufficient surface corrosion resistance of metal sealed stacking rings under high pressure, high frequency dynamic loads and complex working conditions are solved, and a sealed stacking ring with high airtightness and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510324317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
The existing metal sealed stacking rings have problems such as bending process defects, risk of processing cracking and insufficient surface corrosion resistance under high pressure, high frequency dynamic loads and complex working conditions.
The high-air-tight sealed stacking ring was prepared by using Si element microalloyation (0.3-0.6%) combined with low oxygen annealing (oxygen content ≤50ppm).
The airtightness and corrosion resistance of the sealing stacking ring are significantly improved, the leakage rate is ≤1×10⁻6 Pa·m³/s, and the salt spray life is ≥1200h, which is 3-5 times higher than the traditional solution.
Smart Images

Figure CN119839592A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sealing stack rings, and in particular to a manufacturing method of a high-airtightness sealing stack ring and a sealing stack ring. Background Art
[0002] Metal sealing stack rings need to withstand high pressure, high-frequency dynamic loads and complex working conditions, which requires extremely high material strength, fatigue resistance and sealing surface processing accuracy. The following problems exist in the manufacturing of traditional brass seals: Bending process defects: The amount of springback during Z-bending is large (≥3°), resulting in insufficient sealing surface fit and reduced air tightness; Processing cracking risk: The brass bending zone thinning rate exceeds the limit (>20%), which is prone to micro cracks and affects the service life; Insufficient surface corrosion resistance: The salt spray test life of conventional coatings is only 48-72 hours, which is difficult to meet the requirements of harsh environments.
[0003] Existing technologies, such as the Chinese invention patent with publication number CN103484781A, improve the plasticity of brass by optimizing the annealing process, but do not solve the problem of coordinated control of bending accuracy and coating performance. Therefore, there is an urgent need for a sealing stack ring manufacturing method that takes into account high-precision molding, material strength and long-term corrosion protection. Summary of the invention
[0004] 1. Technical issues to be resolved To solve the above problems, the present invention proposes a manufacturing method of a high-airtightness sealing stack ring and a sealing stack ring, aiming to solve the problems of bending process defects, processing cracking risks and insufficient corrosion resistance of the sealing stack ring surface in the prior art.
[0005] (II) Technical solution The invention discloses a method for manufacturing a high-airtight sealing stack ring, wherein the components of the sealing stack ring are as follows by mass percentage: Cu 64-68%, Si 0.3-0.6%, Zn balance, impurity Pb≤0.02%, impurity Fe≤0.1%; The manufacturing method of the high airtight sealing stack ring comprises the following steps: S100, select H65 brass plate, and verify through a spectroscopic device that the Si content of the H65 brass plate accounts for 0.3-0.6% of the total mass of the sealing stack ring; S200, annealing the H65 brass sheet verified in step S100 using a nitrogen protection annealing device, then soaking the H65 brass sheet in alkaline degreasing liquid using an ultrasonic cleaning device, and then washing and drying the sheet; S300, using a fiber laser cutting device to cut the H65 brass plate processed in step S200, and calibrating the plate position by a CCD visual positioning system. After cutting, the outer diameter is Φ50±0.05mm, the inner diameter is Φ44±0.05mm, and a vibration grinder is used to remove the burrs on the cutting edge, Ra≤1.6μm; S400, using a progressive die to stamp the plate after the burrs are removed in step S300, wherein the progressive die stamping includes three stages: punching, pre-bending, and final bending, wherein the upper die R angle is 0.6 mm, the pressure is 80 kN, the bending angle is 30±1° during pre-bending, the compensation angle is 88°, the pressure is 120 kN, the rebound compensation amount is 2°, and the step difference is 1.8±0.03 mm during final bending, and finally a ring body is obtained; S500, using an aging furnace to keep the ring body obtained in step S400 warm, and then cooling it to room temperature by air; S600, the sealing surface is cut by CNC precision machining, the cut ring body is pre-nickel plated, and then gold-imitation electroplating and sealing treatment are performed to obtain a sealing stacked ring.
[0006] In the present invention, the oxygen content in the nitrogen protection annealing device in step S200 should be ≤50ppm, and the temperature should be kept at 450°C for 30 minutes. When the temperature in the device drops to 200°C, it is cooled to room temperature by air; The alkaline degreasing solution includes NaOH and Na2CO3, wherein the content of NaOH is 50 g / L and the content of Na2CO3 is 30 g / L. The H65 brass plate is immersed in the alkaline degreasing solution at 60° C. for 5 minutes.
[0007] In the present invention, the medium used in the vibration grinder in step S300 is ceramic balls.
[0008] In the present invention, the step S400 also includes hydraulic shaping of the ring body. During the hydraulic shaping, the pressure needs to be maintained for 5 seconds to eliminate local stress and ensure that the thickness reduction rate of the bending area is ≤15%.
[0009] In the present invention, the CNC machine tool spindle speed for cutting in step S600 is 1500 rpm, the feed rate is 0.1 mm / r, and the cutting depth is 0.05 mm; During pre-nickel plating, the ring body is pre-plated with a Watt nickel solution, wherein the neutral value of the Watt nickel solution is pH 4.0, the temperature is 55° C., the cathode moving speed during pre-nickel plating is 2 m / min, the current density is 3 A / dm²×5 min, and the plating thickness is 3±0.5 μm; The composition of the gold-imitation electroplating solution is 35g / L CuCN, 10g / L ZnO, 8g / L Na2SnO3, pH value is 12.5, the temperature of the plating solution is 55°C, the cathode current density is 1.5A / dm²×90s, and the coating thickness is 2±0.3μm.
[0010] In the present invention, after the imitation gold plating is completed, the sealing stack ring is immersed in a molybdate solution for 60 seconds and then dried by hot air at 80° C. to increase the corrosion resistance of the sealing stack ring.
[0011] Another sealing stack ring of the present invention is manufactured by the manufacturing method of the high-airtightness sealing stack ring described in the above technical solution, and the sealing stack ring includes a tail portion, a bending portion and a head portion, the end of the head portion is provided with a first notch, the end of the tail portion is provided with a second notch, and the first notch and the second notch are both arranged toward the bending portion.
[0012] In the present invention, the head portion is arranged on one side of the bending portion, and the tail portion is arranged on the other side of the bending portion.
[0013] (III) Beneficial effects Compared with the prior art, the present invention has the following beneficial effects: In the present invention, Si element microalloying (0.3-0.6%) combined with low oxygen annealing (oxygen content ≤ 50ppm), the grain size ≥ 8 levels, the leakage rate ≤ 1×10⁻ 6 Pa·m³ / s, salt spray life ≥1200h, 3-5 times higher than traditional solutions.
[0014] The hydraulic shaping in the present invention reduces the bending thinning rate to ≤15%, the step tolerance is ±0.03mm, avoids micro cracks and ensures the fit of the sealing surface. The adhesion of the coating is effectively increased by pre-nickel plating, imitation gold electroplating, and molybdate sealing, and the salt spray resistance is improved to ≥1000h, breaking through the bottleneck of less than 72h of the traditional coating life. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 A process logic diagram of the manufacturing method; Figure 2 This is a metallographic diagram of the plate after annealing in Example 1; Figure 3 Schematic diagram of the metallographic structure of the sealing stack ring in Example 1; Figure 4 It is a schematic diagram of the three-dimensional structure of the sealing stack ring.
[0017] 10. Head, 101. First notch, 20. Bend, 30. Tail, 301. Second notch. DETAILED DESCRIPTION
[0018] Example 1
[0019] like Figure 1-Figure 3 As shown, a method for manufacturing a high-airtightness sealing stack ring is disclosed. In this embodiment, the components of the sealing stack ring are as follows by mass percentage: Cu 66%, Si 0.5%, Zn balance, impurity Pb ≤ 0.015%, impurity Fe ≤ 0.08%; The manufacturing method of the high-airtightness sealing stack ring comprises the following steps: S100, material selection: select H65 brass plate with a thickness of 1.21 mm. Use a spectrometer, such as an Olympus XRF analyzer, to verify that the Si content of the H65 brass plate accounts for 0.5% of the total mass of the sealing stack ring; S200, material pretreatment: anneal the H65 brass sheet verified in step S100 at 450°C for 30 minutes in a nitrogen protection annealing furnace, and after completion, air cool the interior of the nitrogen protection annealing furnace after the ambient temperature reaches 200°C, so that the temperature of the H65 brass sheet drops to room temperature. In particular, it is necessary to keep the oxygen content in the nitrogen protection annealing furnace ≤50ppm in real time.
[0020] Then, an ultrasonic cleaning device is used to soak the H65 brass plate in an alkaline degreasing solution, and then the plate is washed with water and dried; The alkaline degreasing solution is composed of NaOH and Na2CO3, and the content of NaOH is 50g / L and the content of Na2CO3 is 30g / L. The H65 brass plate is immersed in the alkaline degreasing solution at 60°C for 5 minutes to complete the pretreatment of H65 so that it meets the requirement of grain size ≥8 (detected by metallographic microscope).
[0021] S300, precision blanking: Use a fiber laser cutting machine to cut the H65 brass sheet processed in step S200. The CCD visual positioning system calibrates the sheet position. In particular, the fiber laser cutting machine is TRUMPF TruLaser 5030, which needs to be equipped with a nitrogen auxiliary system to prevent oxidation of the cutting surface during cutting. The power during cutting is 2kW, the cutting speed is 4m / min, the nitrogen pressure is 0.8MPa, and the focus position is ±0.1mm.
[0022] After cutting, the outer diameter is Φ50.02mm and the inner diameter is Φ44.03mm. The burrs on the cutting edge are removed using a vibration grinder, and Ra≤1.6μm. The grinding medium of the vibration grinder is ceramic balls. S400, Z-type bending forming: the plate after the burrs are removed in step S300 is processed by progressive die stamping, and the progressive die stamping includes three stages: punching, pre-bending, and final bending. In the pre-bending, the upper die R angle is 0.6mm, the pressure is 80kN, and the bending angle is 30°. In particular, the bending angle is fed back in real time through the angle sensor. The compensation angle is 88°, the pressure is 120kN, the rebound compensation is 2°, and the step difference is 1.8±0.03mm.
[0023] After completing the three-level Z-bending, the pressure is maintained for 5 seconds by a four-column hydraulic press (pressure is 150kN) to eliminate local stress and ensure that the thickness reduction rate of the bending area is ≤15%, and finally a ring body is obtained.
[0024] S500, aging strengthening treatment: the ring body obtained in step S400 is kept warm in an aging furnace. In particular, the ring body obtained in step S400 is kept warm in an aging furnace at 260° C. for 2 hours, and then air-cooled to room temperature to achieve a hardness of HV125.
[0025] S600, CNC precision machining and surface composite plating: CNC precision machining is used to cut the sealing surface, the cut ring body is pre-nickel plated, and then gold-imitation electroplating and sealing treatment are performed to obtain a sealing stacked ring.
[0026] In step S600, the CNC machine tool spindle speed is 1500 rpm, the feed rate is 0.1 mm / r, and the cutting depth is 0.05 mm; During pre-nickel plating, the ring body is pre-plated with a Watt nickel solution, wherein the neutral value of the Watt nickel solution is pH 4.0, the temperature is 55° C., the cathode moving speed during pre-nickel plating is 2 m / min, the current density is 3 A / dm²×5 min, and the coating thickness is 3.2 μm; The composition of the plating solution for imitation gold electroplating is 35g / L CuCN, 10g / L ZnO, 8g / L Na2SnO3, pH value is 12.5, the temperature of the plating solution is 55℃, the cathode current density is 1.5A / dm²×90s, and the coating thickness is 2.1μm.
[0027] After the imitation gold plating is completed, the sealing stack ring is immersed in a molybdate solution for 60 seconds and then dried by hot air at 80° C. to increase the corrosion resistance of the sealing stack ring.
[0028] like Figure 4As shown, this embodiment also discloses a sealing stack ring, comprising a tail portion, a bending portion and a head portion, wherein a first notch is provided at the end of the head portion, a second notch is provided at the end of the tail portion, and both the first notch and the second notch are provided toward the bending portion. The head portion is provided on one side of the bending portion, and the tail portion is provided on the other side of the bending portion.
[0029] Example 2
[0030] The difference from Example 1 is that the composition of the sealing stack ring is as follows by mass percentage: Cu 64%, Si 0.3%, Zn balance, impurity Pb ≤ 0.02%, impurity Fe ≤ 0.1%; When the material is pretreated in step S200, the H65 brass sheet verified in step S100 is annealed at 440°C for 35 minutes in a nitrogen protection annealing furnace. After the ambient temperature in the nitrogen protection annealing furnace reaches 200°C, the furnace is air-cooled to reduce the temperature of the H65 brass sheet to room temperature.
[0031] The power of laser cutting in step S300 is 2.2 kW, the cutting speed is 3.8 m / min, and the outer diameter after cutting is Φ50.05 mm and the inner diameter is Φ44.05 mm.
[0032] In step S400, the pre-bend is 32°, the final bend is 87° compensation angle, the step difference is 1.78 mm, and the thinning rate is 14%.
[0033] In step S500, the thickness of the imitation gold electroplating layer is 1.9 μm.
[0034] Example 3
[0035] The difference from Example 1 is that the composition of the sealing stack ring is as follows by mass percentage: Cu 68%, Si 0.6%, Zn balance, impurity Pb ≤ 0.01%, impurity Fe ≤ 0.05%; When the material is pretreated in step S200, the H65 brass sheet verified in step S100 is annealed at 460°C for 25 minutes in a nitrogen protection annealing furnace. After the ambient temperature in the nitrogen protection annealing furnace reaches 200°C, the furnace is air-cooled to reduce the temperature of the H65 brass sheet to room temperature.
[0036] In step S400, the final bending angle is 89°, the step difference is 1.83 mm, and the thinning rate is 11%.
[0037] In step S500 , the thickness of the pre-plated nickel layer is 3.5 μm.
[0038] Example 4
[0039] The difference from Example 1 is that the composition of the sealing stack ring is as follows by mass percentage: Cu 65%, Si 0.4%, and Zn balance; The cutting speed during laser cutting in step S300 is 4.2 m / min, and the outer diameter after cutting is Φ49.98 mm.
[0040] In step S400, the hydraulic shaping pressure is 160 kN and the step difference is 1.79 mm.
[0041] Example 5
[0042] The difference from Example 1 is that, in step S200, when the material is pretreated, the H65 brass sheet verified in step S100 is annealed at 430°C for 40 minutes in a nitrogen protection annealing furnace, and after completion, the ambient temperature in the nitrogen protection annealing furnace is cooled by air after reaching 200°C, so that the temperature of the H65 brass sheet drops to room temperature. And the final grain size is ≥9 levels.
[0043] In step S500, the temperature of the imitation gold electroplating solution is 60°C, and the thickness of the plating layer is 2.3 μm.
[0044] Example 6
[0045] The difference from Example 1 is that the composition of the sealing stack ring is as follows by mass percentage: Cu 66%, Si 0.55%, Zn balance, impurity Pb ≤ 0.015%, impurity Fe ≤ 0.07%; In step S400, the pre-bend is 28° and the final bend is 86° compensation angle.
[0046] Example 7
[0047] The difference from Example 1 is that in step S600 , the thickness of the oxide film after molybdate sealing is 0.5 μm.
[0048] Example 8
[0049] The difference from Example 1 is that the composition of the sealing stack ring is as follows by mass percentage: Cu 66%, Zn balance, impurity Pb≤0.015%, impurity Fe≤0.07%; that is, compared with Example 1, no Si is added in this embodiment.
[0050] In step S200 , the annealing temperature is 450° C., and in step S400 , the final bend is 90° (without compensation angle).
[0051] Example 9
[0052] The difference from Example 1 is that in step S200, during annealing, the oxygen content in the nitrogen-protected annealing furnace is 200 ppm, the annealing temperature is 450° C. and the duration is 30 minutes.
[0053] Example 10
[0054] The difference from Example 1 is that the hydraulic step is missing in step S400, and the aging treatment in S500 is directly performed. Comparative analysis of technical effects: 1. Improvement of performance by Si element Example 1-7: Si content 0.3-0.6%, grain size ≥ 8, thinning rate ≤ 15%, leakage rate ≤ 1×10⁻ 6 Pa·m³ / s.
[0055] Example 8 (Si-free): grain coarsening (level 6.5), thinning rate 22%, leakage rate deteriorated to 5×10⁻ 5 , the salt spray life is only 240h.
[0056] Conclusion: Si element significantly improves sealing and corrosion resistance by refining grains and inhibiting crack propagation.
[0057] 2. Annealing oxygen content control Example 1: oxygen content ≤50ppm, grain size 8.5, hardness HV125.
[0058] Example 9 (oxygen content 200 ppm): The grains were coarsened to level 6.0, the hardness dropped to HV100, and the salt spray life was only 500 h.
[0059] Conclusion: Low oxygen annealing avoids oxidation embrittlement and ensures material plasticity and coating adhesion.
[0060] 3. Necessity of hydraulic shaping Example 1: Step difference 1.81mm (tolerance ±0.03mm), leakage rate 8×10⁻ 7 .
[0061] Example 10 (unshaped): step difference 1.92mm (exceeding tolerance +6.7%), leakage rate 2×10⁻ 5 .
[0062] Conclusion: 150kN pressure is maintained for 5 seconds to eliminate stress and ensure dimensional accuracy and air tightness.
[0063] 4. Synergistic effect of composite coating Example 1: Imitation gold plating (2.1μm) + molybdate sealing, salt spray life 1200h.
[0064] Example 8: No Si resulted in coating adhesion 1B, and peeling after 240 hours.
[0065] Conclusion: Pre-nickel plating and imitation gold electroplating form a dense protective layer, which combined with sealing treatment can extend the corrosion resistance life.
[0066] This solution achieves a synergistic improvement in air tightness, corrosion resistance, and mechanical properties through innovative processes such as Si microalloying, low-oxygen annealing, and hydraulic shaping.
[0067] The above-described embodiments are merely descriptions of preferred implementations of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made by ordinary persons in the art to the technical solution of the present invention should fall within the protection scope of the present invention, and the technical contents for which protection is sought in the present invention have been fully recorded in the claims.
Claims
1. A method for manufacturing a high-airtight sealing stack ring, characterized in that: The composition of the sealing stack ring is as follows by mass percentage: Cu 64-68%, Si 0.3-0.6%, Zn balance, impurity Pb≤0.02%, impurity Fe≤0.1%; The manufacturing method of the high-airtightness sealing stack ring comprises the following steps: S100, select H65 brass plate, and verify through a spectrometer that the Si content of the H65 brass plate accounts for 0.3-0.6% of the total mass of the sealing stack ring; S200, annealing the H65 brass sheet verified in step S100 using a nitrogen protection annealing device, then soaking the H65 brass sheet in alkaline degreasing liquid using an ultrasonic cleaning device, and then washing and drying the sheet; S300, using a fiber laser cutting device to cut the H65 brass plate processed in step S200, and calibrating the plate position by a CCD visual positioning system. After cutting, the outer diameter is Φ50±0.05mm, the inner diameter is Φ44±0.05mm, and a vibration grinder is used to remove the burrs on the cutting edge, Ra≤1.6μm; S400, using a progressive die to stamp the plate after the burrs are removed in step S300, wherein the progressive die stamping includes three stages: punching, pre-bending, and final bending, wherein the upper die R angle is 0.6 mm, the pressure is 80 kN, the bending angle is 30±1° during pre-bending, the compensation angle is 88°, the pressure is 120 kN, the rebound compensation amount is 2°, and the step difference is 1.8±0.03 mm during final bending, and finally a ring body is obtained; S500, using an aging furnace to keep the ring body obtained in step S400 warm, and then cooling it to room temperature by air; S600, the sealing surface is cut by CNC precision machining, the cut ring body is pre-nickel plated, and then gold-imitation electroplating and sealing treatment are performed to obtain a sealing stacked ring.
2. The method for manufacturing a high-airtight sealing stack ring according to claim 1, characterized in that: In the step S200, the oxygen content in the nitrogen protection annealing device should be ≤50ppm, and the temperature should be kept at 450°C for 30 minutes. When the temperature in the device drops to 200°C, it is cooled to room temperature by air; The alkaline degreasing solution includes NaOH and Na2CO3, wherein the content of NaOH is 50 g / L and the content of Na2CO3 is 30 g / L. The H65 brass plate is immersed in the alkaline degreasing solution at 60° C. for 5 minutes.
3. The method for manufacturing a high-airtight sealing stack ring according to claim 2, characterized in that: The medium used in the vibration grinder in step S300 is ceramic balls.
4. The method for manufacturing a high-airtight sealing stack ring according to claim 3, characterized in that: The step S400 also includes hydraulic shaping of the ring body. During the hydraulic shaping, the pressure needs to be maintained for 5 seconds to eliminate local stress and ensure that the thickness reduction rate of the bending area is ≤15%.
5. The method for manufacturing a high-airtight sealing stack ring according to claim 4, characterized in that: The CNC machine tool spindle speed for cutting in step S600 is 1500 rpm, the feed rate is 0.1 mm / r, and the cutting depth is 0.05 mm; During pre-nickel plating, the ring body is pre-plated with a Watt nickel solution, wherein the neutral value of the Watt nickel solution is pH 4.0, the temperature is 55° C., the cathode moving speed during pre-nickel plating is 2 m / min, the current density is 3 A / dm²×5 min, and the plating thickness is 3±0.5 μm; The composition of the gold-imitation electroplating solution is 35g / L CuCN, 10g / L ZnO, 8g / L Na2SnO3, pH value is 12.5, the temperature of the plating solution is 55°C, the cathode current density is 1.5A / dm²×90s, and the coating thickness is 2±0.3μm.
6. The method for manufacturing a highly airtight sealing stack ring according to claim 5, characterized in that: After the imitation gold plating is completed, the sealing stack ring is immersed in a molybdate solution for 60 seconds and then dried by hot air at 80° C. to increase the corrosion resistance of the sealing stack ring.
7. A sealing stack ring, characterized in that: The sealing stack ring is manufactured by the manufacturing method of the high-airtightness sealing stack ring according to any one of claims 1 to 6, and the sealing stack ring includes a tail portion, a bending portion and a head portion, the end of the head portion is provided with a first notch, the end of the tail portion is provided with a second notch, and the first notch and the second notch are both arranged toward the bending portion.
8. The sealing stack ring according to claim 7, characterized in that: The head portion is arranged on one side of the bending portion, and the tail portion is arranged on the other side of the bending portion.
Citation Information
Patent Citations
High-strength and high-toughness spring steel and manufacturing method thereof
CN103484781A
Preparation method of stainless steel pipe for sealing ring with high resilience
CN107904378A
Manufacturing method of spiral check ring
CN111015129A
Metal pressure-regulating sealing ring and processing method thereof
CN117570202A
Exhaust sealing ring heat treatment processing method
CN117625932A